2022
DOI: 10.1101/2022.01.07.22268899
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mendelian gene identification through mouse embryo viability screening

Abstract: The diagnostic rate of Mendelian disorders in sequencing studies continues to increase, along with the pace of novel disease gene discovery. However, variant interpretation in novel genes not currently associated with disease is particularly challenging and strategies combining gene functional evidence with approaches that evaluate the phenotypic similarities between patients and model organisms have proven successful. A full spectrum of intolerance to loss-of-function variation has been previously described, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 81 publications
(115 reference statements)
1
4
0
Order By: Relevance
“…Robbins et al suggested that lethality occurring early in the pregnancy would involve genes related to fundamental cellular processes, while genes associated to developmental biological processes would be associated to death occurring at a later fetal developmental stage 39 . The analysis of mouse knockout lethal genes confirms the association between the embryonic stage at which lethality occurs and the different biological processes ascribed to each corresponding genes 5,30 .…”
Section: The Challenge Of Identifying Lethal Genes In Humans: Diagnos...supporting
confidence: 52%
See 3 more Smart Citations

Lethal phenotypes in Mendelian disorders

Cacheiro,
Lawson,
Van den Veyver
et al. 2024
Preprint
Self Cite
“…Robbins et al suggested that lethality occurring early in the pregnancy would involve genes related to fundamental cellular processes, while genes associated to developmental biological processes would be associated to death occurring at a later fetal developmental stage 39 . The analysis of mouse knockout lethal genes confirms the association between the embryonic stage at which lethality occurs and the different biological processes ascribed to each corresponding genes 5,30 .…”
Section: The Challenge Of Identifying Lethal Genes In Humans: Diagnos...supporting
confidence: 52%
“…fetal hydrops, a unique severe often lethal prenatal phenotype can be associated to cardiovascular, immunological, or the haematological category. More granular associations can also be found when we explore the exact embryonic stage at which the mouse embryo dies 30 .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations

Lethal phenotypes in Mendelian disorders

Cacheiro,
Lawson,
Van den Veyver
et al. 2024
Preprint
Self Cite
“…The effect of cell essentiality or lethality can apply to generating lines with disease-associated variants such as single nucleotide variants. Given the high proportion of essential genes among human disease genes 19,27 , generating mouse models of human disease may require preserving one copy of the wild-type allele, that is producing heterozygous founders or conditional variant alleles, to establish a new mouse line. Overall, the use of Cas9 is a robust and flexible method to generate gene-edited mouse lines.…”
Section: Discussionmentioning
confidence: 99%